Northern Ireland: living with the crisis - Ward, Alan J. (Praeger, 1987)
Introduction. The impact of the Northern Ireland crisis on the economy / N.J. Gibson -- Psychological well-being in Northern Ireland / Karen Trew -- The impact of the troubles on the law and legal system of Northern Ireland / D.S. Greer -- The Northern Ireland electorate / Joseph E. Thompson -- The faith and its forms in times of strife / Eric Gallagher -- Catholics, Catholicism, and the Northern Ireland crisis / Gary MacEoin -- "Words at once both gaff and bait" : the writer's response to Northern Ireland / Joseph Browne -- Poets and culture : Seamus Heaney, Derek Mahon, and Tom Paulin / Terence Brown -- "No petty people" : William Trevor and the Anglo-Irish dimension ... / Robert E. Rhodes -- Community conscience of reflection? : theatre in Northern Ireland / Claudia Harris